Clustering Kualitas Kinerja Pegawai Pemerintah Dengan Perjanjian Kerja Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kota Bengkulu - Wahyu Ishak Marzuki; Herlina Latipa Sari; Yupianti Yupianti (Jurnal Media Infotama, 2023)
Abstract-The performance of Government Employees with Work Agreements (PPPK) is one of the elements that greatly determines the quality of PUPR services. With this very important function, PPPK performance needs to be managed properly to determine whether PPPK professionalism has been maximized. One way is by using the Clustering technique with the K-Means algorithm which is very fast in the process of grouping potential PPPK performance. This research method uses SDLC (System Development Life Cycle), which is a logical process used by systems analysts to describe an information system, including requirements, validation, training and ownership. The end result of this research is a system that can cluster PPPK performance into 3 parts where the Best Performance Quality consists of 7 people, Fairly Good Performance Quality consists of 1 person and Poor Performance Quality consists of 7 people.